Hekarella talawakelae gen. and sp. nov., a curious new genus and species of monogonant Carnoyidae (Nematoda:Rhigonematida) from Sri Lanka - Hunt, David J.; Mohotti, Keerthi Meepe (Muzeum i Instytut Zoologii PAN, 2000)
Hekarella talawakelae, a new genus and species of rhigonematid from the Carnoyidaeis described from the gut of a diplopod from Sri Lanka. The new genus is characterised by the presence of four, well developed, sublateral longitudinal rows of spines in the cervical region of the female, the presence of six cuticularised pieces around the oral opening, the monogonant female genital system, no cephalic cap in the male, anisomorphic and anisometric spicules, boat-shaped gubernaculum with a dorsal hole and 15 copulatory papillae with three pairs either sublateral, subdorsal. Hekarellagen. nov. has some morphological affinities with Martadamsonius, an Africancarnoyid and also with the Indian genus Raonema, but is easily differentiated by the presence ofonly one genital tract and by the form of the markedly anisomorphic and anisometric spicules.
Incorrect ISSN 0001-6454
Bibliogr. p. 246
P. 239-246 : ill. ; 24 cm
Keywords: nematodes; Nematoda; morphology; new genus; new species; SEM; Sri Lanka; taxonomy